2022
DOI: 10.3390/jcm11041071
|View full text |Cite
|
Sign up to set email alerts
|

IDELVION: A Comprehensive Review of Clinical Trial and Real-World Data

Abstract: Hemophilia B is a bleeding disorder caused by a deficiency of coagulation factor IX (FIX). Treatment with FIX replacement products can increase FIX activity levels to minimize or prevent bleeding events. However, frequent dosing with standard-acting FIX products can create a high treatment burden. Long-acting products have been developed to maintain bleed protection with extended dosing intervals. Recombinant factor IX–albumin fusion protein (rIX-FP) is a long-acting product indicated for the treatment and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…During the 2 weeks after surgery, the patient required low FIX doses (147.5 IU/kg of rIX‐FP), which was considerably lower than the median dose of 221.7 (0–444.07) IU/kg reported by Curtin et al 17 Nevertheless, it should be mentioned that the patient was also maintained on antiplatelet therapy after surgery. These results further support the evidence that EHL products, such as rIX‐FP, offer a promising alternative to standard half‐life (SHL) drugs in patients undergoing surgery, as they reduce the number of infusions, doses, and costs, especially in the case of EHL FIX 34 …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…During the 2 weeks after surgery, the patient required low FIX doses (147.5 IU/kg of rIX‐FP), which was considerably lower than the median dose of 221.7 (0–444.07) IU/kg reported by Curtin et al 17 Nevertheless, it should be mentioned that the patient was also maintained on antiplatelet therapy after surgery. These results further support the evidence that EHL products, such as rIX‐FP, offer a promising alternative to standard half‐life (SHL) drugs in patients undergoing surgery, as they reduce the number of infusions, doses, and costs, especially in the case of EHL FIX 34 …”
Section: Discussionsupporting
confidence: 73%
“…These results further support the evidence that EHL products, such as rIX-FP, offer a promising alternative to standard half-life (SHL) drugs in patients undergoing surgery, as they reduce the number of infusions, doses, and costs, especially in the case of EHL FIX. 34 VETs with ROTEM and Quantra were especially useful to evaluate the global hemostatic status during the perioperative process, allowing us to analyze components such as platelet and fibrinogen levels, beyond the effect of FIX levels. In addition, VET proved very useful for monitoring the effect of heparin during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Further, FcRn expression in endothelial cells and monocytes is responsible for albumin recycling and maintenance of its high levels in the circulation 68,69,210 . As a novel therapeutic approach, engineered albumin and albumin-fusion proteins are increasingly becoming well-accepted alternatives to engineered Fc and Fc fusions, which use FcRn functions without having the risk of engaging FcγRs, with factor IX-albumin fusion (albutrepenonacog alfa) 211 being a prime example. of its roles in recycling and transcytosis 20,23 (Figs.…”
Section: Fcrn As An Albumin Receptormentioning
confidence: 99%
“…Previous clinical studies demonstrated that prophylaxis with rIX-FP significantly reduced the risk of spontaneous and total bleedings, helped controlling haemostasis in the perioperative settings, and contributed to joint function preservation [3,5–9]. In all trials, rIX-FP was well tolerated by paediatric, adolescent and adult patients with severe haemophilia, with no reports of inhibitor development and resulting in substantial improvements in HR-QoL [1,3,14 ▪▪ ]. Moreover, switching from a nonacog-alfa therapy to an rIX-FP was associated with maintenance of clinical benefits and decreased frequency and FIX consumption without adverse events [10].…”
Section: Introductionmentioning
confidence: 95%
“…once every 3 or 4 days) to maintain protective FIX levels. In the past years, the first genetically recombinant fusion of rFIX with another protein - a recombinant human albumin – was developed (albutrepenonacog-alfa or rIX-FP; IDELVION) as a strategy to extend the t 1/2 of rFIX-FP (around 95 h) [2–4,14 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%